Tontura em idosos institucionalizados da cidade do NATAL/RN: Um estudo caso-controle em vestibulopatas e não-vestibulopatas - Ferreira, Lidiane Maria de Brito Macedo (2013)
the institutionalized elderly presents for being more fragile a lot of body balance s changes, which can induce falls and health frailty. One of the consequences of it is the appearance of dizziness, vestibular or not. This study aims to identify the risk factors related to dizziness in institutionalized elderly, with and without vestibular disorders, in the city of Natal-RN. Method: a case-control study realized in 12 regulated by Health Surveillance Long Term Care Institutions for the elderly in Natal-RN. Elected seniors with good cognitive level and able to walk, totaling 115 individuals, and of these, 102 were selected according to the presence of dizziness in the last year (n = 51) and their controls (n = 51), paired by sex and age. The 51 elderly patients with dizziness were divided into 3 groups case: case one, for elderly with dizziness and without vestibulopathy (n=38); case two, for elderly with dizziness and vestibulopathy (n=13) and case three, for all the seniors with dizziness, or added to the case 1 case 2 (n=51). The 51 seniors who served as controls were also divided into three groups, according to the number of individuals of each case: control 1, n = 38, control 2, n = 13 control and 3 (sum of 1 control with control 2), n = 51. As possible risk factors were analyzed variables related to characteristics of the institution, to the habits of life of older people and those concerned with the health of the elderly. For statistical analysis, we used the chi-square or Fisher exact test for a significance level of 5% and calculating the association magnitude between variables by measuring the Odds Ratio. Results: as risk factors for dizziness without vestibular disorders were found the presence of hypertension and cardiovascular disease, as well as the presence of three or more disorders for elderly and use of gastric protector drugs. For the elderly group from case two were found no associated risk factor. For elderly patients with dizziness in the case group three, we observed the same risk factors found for the elderly in the case group one, plus the presence of osteoarthritis pathology, which was also significant for this group. Conclusion: dizziness in institutionalized elderly is associated with systemic common diseases in this age group and the vestibulopathy presents itself as pathology on an isolated way, not being possible, with our data, associate it with non-risk factors